Antimicrobial control and temporal dynamics of M. plutonius colonization in adult worker honey bees (Apis mellifera) - Midhun Sebastian Jose; Marina Carla Bezerra da Silva; Oleksii Obshta; Fatima Masood; Jenna M. Thebeau; Sarah Biganski; Muhamad Fahim Raza; Marcelo Polizel Camill; E.E. Tellarini Prieto; Thanuri Edirithilake; Ivanna Kozii; Igor Moshynskyy; et al. (PLoS ONE, 2025)
European foulbrood (EFB) is a stress-associated brood disease affecting honey bee larvae, caused by infection with Melissococcus plutonius. Adult bees are suggested to be a reservoir for this bacterium; however, the duration of M. plutonius colonization of adult bees and its impact on adult bee survival remain inadequately understood. In North America, the only approved antimicrobial for treatment of EFB is oxytetracycline; yet the antimicrobials tylosin and lincomycin are also widely used in beekeeping. The effect of these antimicrobials on M. plutonius colonization of adult bees is unclear. To investigate these unknowns, we infected summer and winter adult worker bees with M. plutonius in the laboratory and treated the infected workers with one of three used antibiotics in beekeeping, in either the laboratory, or within field colonies. We found that worker bees remained persistently infected with M. plutonius for at least 22–38 days in the laboratory and at least 24 days in field colonies. Moreover, M. plutonius ingestion was associated with a significant, dose-dependent decrease in adult worker survival. Antibiotic treatment significantly decreased the M. plutonius load of colonized adult workers but failed to eliminate M. plutonius; still antibiotic treatment improved the survival of bees in the laboratory cages. Taken together, these findings indicate the importance of adult bees as a reservoir of M. plutonius, even in colonies treated with antimicrobials.